An investigation into conceptual metaphor denoting love in “the thorn birds” by colleen mccullough and in its vietnamese translational version - Nguyễn,Thị Ngọc Trâm; Phan Văn Hòa (ĐHĐN : ĐHĐN., 2015)
This study mainly focuses on analyzing the conceptual metaphor denoting love in “The Thorn Birds” by Colleen McCullough and in its Vietnamese translational version by Pham Manh Hung, and gives the metaphorical mappings. We investigate the conceptual metaphor denoting the concept of love in the original novel and in Vietnamese translational version based on the theory of conceptual metaphor and we categorize the conceptual metaphor of love into groups and analyze the conceptual metaphor in term of meaning and structure mapping. The metaphorical mapping such as love is an entity, a war, fire, a natural force, a physical force, rapture/ a high, insanity and a fluid in a container will be analyzed in our study. And we find out the similar expressions of conceptual metaphor denoting love in the original novel and in the translational version, give the differences about syntactic features of conceptual metaphor denoting love in two languages.This study also suggests some implications for learners and readers. This helps learner have the best way to learn how and when the love from context because conceptual metaphor denoting love denotes more than one emotional state and understand conceptual metaphor not only in literature but also in the life.
Keywords: conceptual metaphor denoting love in “the thorn birds” by colleen mccullough and in its vietnamese translational version; conceptual metaphor denoting -- vietnamese translational version